Capacitively coupled contactless conductivity detection for analytical techniques - Developments from 2018 to 2020 - Hauser, Peter C; Kubáň, Pavel (Journal of chromatography. A, 2020)
The developments of analytical contactless conductivity measurements based on capacitive coupling over the two years from mid-2018 to mid-2020 are covered. This mostly concerns applications of the technique in zone electrophoresis employing conventional capillaries and to a lesser extent lab-on-chip devices. However, its use for the detection in several other flow-based analytical methods has also been reported. Detection of bubbles and measurements of flow rates in two-phase flows are also recurring themes. A few new applications in stagnant aqueous samples, e.g. endpoint detection in titrations and measurement on paper-based devices, have been reported. Some variations of the design of the measuring cells and their read-out electronics have also been described.
Keywords: Industry; voda; elektrická vodivost; Capacitively coupled contactless conductivity detection; Microchip electrophoresis; Electrophoresis, Capillary; Animals; elektroforéza kapilární; Food Analysis; Electric Conductivity; Capillary electrophoresis; průmysl; Water; zvířata; Review; analýza potravin